Analisis Bibliometrik Trend Penelitian Pemodelan Matematis Menggunakan Database Google Scholar, Publish or Perish, dan Vosviewer - Komang Ariyanto (Lembaga Intelektual Muda (LIM) Maluku, 2023)
This study aims to identify the topic of the study of mathematical modeling by highlighting publications on Google Scholar from 1951 to 2022. This study uses the Google Scholar citation database for 71 years to collect articles. The keyword used in this research is